Riding the "HTS" wave : information cascades in the viewership of online videos. - Sim, Clarice Chwei Lin. (2010)
The exploding spread of online peer-posted videos on platforms such as YouTube has been phenomenal. Despite the widespread usage of online videos, the demand dynamics of the online video market is not sufficiently understood. One feature available on all video-sharing websites is popularity indicators which display the cumulative realized demand for a given video. The sharing and viewing of online videos are hypothesized to be influenced by the process of information cascades, which commonly affect the consumption choices of patrons among (content) products with high levels of quality uncertainty. The presence of information cascades is characterized by convergent behavior, where sequential patrons defer to the choices made by preceding others. The extent to which cascading occurs is further dependent on the level of content quality uncertainty. Specifically, we hypothesize that a lower level of quality uncertainty allows audiences to directly infer video quality which then dampens the cascading effect.